Versatility of Radial Forearm Free Flap in Reconstruction of Buccal Defect (Medicine Today, 2015)
The ideal method for buccal defects reconstruction should provide good outcome of both function and appearance; our goal is to highlight the reliability of radial forearm flap in buccal reconstruction. This retrospective study was conducted from July 2013 to June 2014, 04 radial forearm flaps were used to repair the defects. We analyzed the superiority and reliability of the flap; in addition, we reviewed some related literature. All radial forearm flaps totally survived. Radial forearm flap is a reliable method for buccal defect reconstruction.Medicine Today 2015 Vol.27(1): 27-29